Protection Over Procedure: Why the Law Requires Divergent Burdens of Proof in Asylum and Withholding of Removal Claims - Alyssa Ruiz (Washington University Journal of Law and Policy, 2026)
In the whirlwind that is asylum and withholding of removal petitions, interpretations of the standards of proof in each statute can mean a matter of life or a lifetime of harm. Nowhere is this axiom more demonstrated than in the Fourth Circuit’s interpretation of the withholding of removal statute’s standard of proof in Diaz-Hernandez v. Garland. The asylum statute’s standard of proof is logically more stringent than that of withholding of removal; the former requires petitioners to demonstrate that their membership in a protected group is the “central reason” behind their persecution, while withholding of removal requires petitioners to demonstrate slightly less: the petitioner’s membership in a protected group is a “reason” behind threats to their lives and freedoms. The Fourth Circuit joined a nationwide circuit split on the interpretation of the standard of proof in both statutes, requiring petitioners to demonstrate the stronger nexus in asylum and withholding of removal. Conversely, the Sixth and Ninth Circuits followed a more correct interpretation of the standard of proof: asylum petitioners must demonstrate a stronger “central reason” behind persecution than withholding of removal petitioners. Despite the varied textual interpretations between the Fourth and the Sixth & Ninth Circuits, petitioners and concerned organizations alike are at a loss. How can lawyers and petitioners prepare evidence and demonstrate the proper connections between their persecution and their membership in protected groups? Concerned organizations have demanded that different burdens for each form of relief be respected, calling attention to the varied benefits and procedural barriers to citizenship that each statute professes. How can petitioners face threats to their lives and still be beholden to a stringent standard of proof when the benefits of the statute are marginal in comparison? Considering the increase in hostility towards immigrants in the United States, this Note analyzes and evaluates the circuit split on the standard of proof interpretation of asylum and withholding of removal, critiques the Fourth Circuit’s application of the standard of proof to its petitioners, and evaluates the social, political, and policy implications of a proper holding in these cases.
Keywords: #AsylumLaw; #WithholdingOfRemoval; #NexusRequirement; #CircuitSplit; #ImmigrationJustice